Evaluasi Kebijakan Pelayanan Peminjaman Sarana dan Prasarana di LPMP Kalimantan Tengah - Noor Kamalla; Nurul Hikmah Kartini; Fitriani Fitriani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
The Central Kalimantan LPMP has goals and objectives that are broadly stated in its vision and mission statement. The vision is the realization of people and ecosystems in primary and secondary education units that are characterized by national standards and have a global perspective through an education quality assurance system based on mutual cooperation. While its mission: 1) Realizing primary and secondary education units with national standards, global outlook, 2) Improving educational standards in primary and secondary education units, 3) Improving education quality assurance services at the provincial level, 4) Realizing quality human beings and having the character of elementary and secondary education units, 5) Improve governance and effectiveness of institutional bureaucracy. The success of LPMP Central Kalimantan in efforts to build good governance can be seen from how well public service policies can satisfy the community. For this reason, an evaluation of public service policies in borrowing infrastructure and infrastructure is needed at the LPMP Kalimantan Tengah. The approach used in this study is the Countenance Evaluation Model / Stake evaluation model. This model was developed by Stake. The Stake Model emphasizes the implementation of two main points, namely (1) description (description) and (2) judgment (judgment), as well as empowering three stages in program evaluation, namely (1) antecedents (context), (2) transactions (transaction/process), and (3) output (output-outcomes). The policy of lending facilities and infrastructure services in Central Kalimantan LPMP can be stated from the beginning (accidents/context) making the objectives and the basis of the policy can already be stated to have reached public service standards, Sarpras and lending schedules are also almost fully meet public service standards. In the part of the transaction where the service process and support/cooperation in the service has also fully met with public service standards. Whereas in the outcomes section where the service results felt by surprise loans have met the target and can be stated to have met public service standards.